HORMONAL CHANGES IN WOMEN WITH MENSTRUAL-OVARIAN DYSFUNCTION CAUSED BY COVID-19 AND INNOVATIVE APPROACHES TO ITS CORRECTION - Shukurov, F.I.; Yuldasheva, N.Z.; Nasriddinova, G.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. COVID-19 has a significant impact on the reproductive system of women, including disrupting the regulation of menstrual-ovarian function. Aim. To study hormonal changes in women with menstrual-ovarian dysfunction caused by COVID-19 and to develop innovative approaches for their correction. Materials and methods. The study included 90 women divided into three groups according to the clinical course of COVID-19: Group I – 20 women with mild disease, Group II – 20 women with moderate severity, and Group III – 20 women with severe COVID-19. A control group of 30 healthy women was also included. Clinical, immunological, hormonal, ultrasound, and statistical methods were used in the study. Results. The study showed that estradiol and progesterone levels decreased in women who had recovered from COVID-19, while levels of FSH, LH, prolactin, and testosterone increased. Among women of reproductive age who had recovered from COVID-19, hypoestrogenism was observed in 57.3%, hyperandrogenism in 17.4%, and hypoprogesteronemia in 25.3% of patients. These findings highlight the importance of an individualized approach to treatment based on identified hormonal deviations. Hormone therapy in women who had recovered from COVID-19 helped restore the ovarian-menstrual cycle in 85.3% of patients with detected hormonal abnormalities. Conclusion. The study results showed that COVID-19 in women of reproductive age causes dysfunction of the hypothalamic-pituitary-ovarian system, leading to menstrual-ovarian function disorders. Corrective hormone therapy using a drug containing 0.060 mg of micronized gestodene and 0.015 mg of ethinylestradiol in women of reproductive age who recovered from COVID-19 contributed to the restoration of menstrual-ovarian function in 85.3% of patients.